Interpretive quantification : methodological explorations for critical and constructivist IR - Barkin, J. Samuel, 1965-; Sjoberg, Laura, 1979- (Ann Arbor : University of Michigan Press, 2017)
"Countering the growing divide between positivists who embrace quantitative, numerical approaches and post-positivist scholars who favor qualitative, interpretive approaches, J. Samuel Barkin and Laura Sjoberg argue that both methods are more widely adaptable than is commonly assumed by either camp. In Interpretive Quantification, ten highly regarded scholars in the field of International Relations apply quantitative methods and formal models to specific constructivist and critical research questions. In this way, each chapter serves not only as evidence that methods can productively be applied across paradigms, but also as a guide as to how this may be done. In sum, the contributors make a compelling case that when researchers cordon off particular methods for merely ideological reasons, they circumscribe their own paradigms and hinder their own research agenda"--
Introduction : why quantitative methods for constructivist and critical theorizing? / J. Samuel Barkin and Laura Sjoberg -- Measuring critical theories of human rights / Brooke Ackerly, with José Miguel Cruz, Anna Carella, and Bishawjit Mallick -- Quantitative methods and constructivist theorizing for conflict studies / Cameron G. Thies -- Exploring constitution and social construction through network analysis / Matthew Hoffman -- Dimensions of identity construction and the measurement of differences among countries / Paul A. Kowert -- Computing narratives : assemblage relations in diplomatic conversations / David Sylvan -- Thinking counterfactually and with discipline : agent-based models for constructing and deconstructing the future / Ian S. Lustick -- Constructing rational international fisheries governance / J. Samuel Barkin -- Theoretical geometry, critical theory, and concept spaces in IR / Laura Sjoberg and Kevin Knudson -- Practicing (social-)scientific pluralism / Patrick Thaddeus Jackson -- Conclusion : prospects for interpretive quantification / J. Samuel Barkin and Laura Sjoberg.
Includes bibliographical references and index.
Description based on print version record; resource not viewed.
eBooks on EBSCOhost
Keywords: International relations -- Research -- Methodology; Quantitative research; Constructivism (Philosophy); Relations internationales -- Recherche -- Méthodologie.; Recherche quantitative; Constructivisme (Philosophie); POLITICAL SCIENCE / History & Theory; POLITICAL SCIENCE / International Relations / General; Constructivism (Philosophy); International relations -- Research -- Methodology; Quantitative research